2012
DOI: 10.1021/ci3001056
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 2D and 3D Structural Features of Drug Molecules in the Prediction of Drug Profile Matching

Abstract: Drug Profile Matching (DPM), a novel virtual affinity fingerprinting method capable of predicting the medical effect profiles of small molecules, was introduced by our group recently. The method exploits the information content of interaction patterns generated by flexible docking to a series of rigidly kept nontarget protein active sites. We presented the ability of DPM to classify molecules excellently, and the question arose, what the contribution of 2D and 3D structural features of the small molecules is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In a following study, we studied the contribution of the structural features of the drugs to the high prediction power of the method. We showed that DPM outperformed conventional two-dimensional and three-dimensional structural similarity-based prediction approaches in almost all examined categories 4. Nevertheless, its prediction accuracy is limited if only a few compounds can be used as a learning set for a given effect.…”
Section: Introductionmentioning
confidence: 92%
“…In a following study, we studied the contribution of the structural features of the drugs to the high prediction power of the method. We showed that DPM outperformed conventional two-dimensional and three-dimensional structural similarity-based prediction approaches in almost all examined categories 4. Nevertheless, its prediction accuracy is limited if only a few compounds can be used as a learning set for a given effect.…”
Section: Introductionmentioning
confidence: 92%
“…[ Peragovics et al, 2012;Simon et al, 2012] Drug-target interactions from chemical and genomic kernels using Bayesian matrix factorization Four drug-target interaction networks involving enzymes, ion channels, G-protein-coupled receptors and nuclear receptors were considered. Authors proposed a novel Bayesian formulation that combines dimensionality reduction, matrix factorization and binary classification for predicting drug-target interaction networks using only chemical similarity between drug compounds and genomic similarity between target proteins.…”
Section: Similarity Ensemble Approach (Sea)mentioning
confidence: 99%
“…The quantitative structure−activity relationship (QSAR) approach is a useful tool for optimizing leads and predicting target/off‐target activities and toxicity. QSAR‐based affinity predictions are useful for the general drug development process, including the repositioning (repurposing) of already approved drugs, poly‐pharmacology, and the prediction of drug−drug interactions . The recent accumulation of protein−compound affinity data in public repositories, such as the PubChem and ChEMBL projects, has enabled us to carry out proteome‐wide target/off‐target predictions ,.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR-based affinity predictions are useful for the general drug development process, including the repositioning (repurposing) of already approved drugs, poly-pharmacology, and the prediction of drugÀdrug interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The recent accumulation of proteinÀcompound affinity data in public repositories, such as the PubChem and ChEMBL projects, has enabled us to carry out proteome-wide target/off-target predictions. [16,17] These predictions are based on QSAR models for multiple proteins, just as in conventional computer-aided drug design and virtual screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation